2018
DOI: 10.1037/ccp0000285
|View full text |Cite
|
Sign up to set email alerts
|

Training clinicians to deliver group CBT to manage anxiety in youth with ASD: Results of a multisite trial.

Abstract: Results suggest that although there may be some advantage to participating in a Workshop, clinicians in all conditions could deliver FYF with excellent fidelity and yield positive treatment outcomes. Lack of a no-treatment comparison group limits interpretation of findings. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…CBTs were previously reported as useful in improving functioning among typically developing students with social phobia [Tillfors et al, ]. Recent randomized controlled studies have also indicated positive effects of CBT on reduction of anxiety symptoms among individuals with ASD [Murphy et al, ; Reaven et al, ; Wise et al, ]. However, most of these studies were conducted with children or adolescents, focused on reduction of different kinds of anxiety, and used generic CBT protocols not specifically designed for treatment of social anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBTs were previously reported as useful in improving functioning among typically developing students with social phobia [Tillfors et al, ]. Recent randomized controlled studies have also indicated positive effects of CBT on reduction of anxiety symptoms among individuals with ASD [Murphy et al, ; Reaven et al, ; Wise et al, ]. However, most of these studies were conducted with children or adolescents, focused on reduction of different kinds of anxiety, and used generic CBT protocols not specifically designed for treatment of social anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, high levels of social anxiety symptoms may result in a diagnosis of social anxiety disorder (SAD), also known as social phobia [Diagnostic and Statistical Manual of Mental Disorders (DSM‐5), APA, ]. Although the high prevalence of anxiety disorders among individuals with ASD has led to studies utilizing cognitive behavioral therapy [CBT; Murphy et al, ; Reaven et al, ; Wise et al, ], most have been conducted with children or adolescents, and have used general CBT protocols not specifically designed for addressing social anxiety. As social anxiety may significantly affect the ability to adapt to everyday independent functioning among students without and with ASD [Kraper, Kenworthy, Popal, Martin, & Wallance, ], remedying this gap in adult ASD research is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The strategies presented in the didactics were chosen from the National Clearinghouse on Autism Evidence and Practice (NCAEP) report on evidence-based practices (Steinbrenner et al, 2020) and included strategies such as visual supports, video modeling, and social narratives that are supported by the current intervention literature (e.g. see Reaven et al, 2018, for a discussion of how to provide community training for mental health clinicians to tailor CBT for autistic clients).…”
Section: Echo Autism Mental Health Modelmentioning
confidence: 99%
“…Further explication of such mechanisms is critical for effective treatment planning. There has been a proliferation of intervention studies targeting anxiety in autism over recent years with evidence for efficacy for standard and modified CBT approaches (Kerns et al, 2016; Reaven et al, 2018; Wood et al, 2015). Recent data emphasize the need for specific attention to IU, including evidence of IU as a predictor of effectiveness for anxiety treatment (Keefer et al, 2017; Rodgers et al, 2016a; Rodgers et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%